Implementasi dan Perancangan Sistem Informasi Penjualan Vapestore Berbasis Mobile Flutter - Ripai, Rizki; Fauzi, Yudiansyah; Sidik, Fazar; Pari, Riki Aldi; Hamdan, Rifky Aditia (Universitas Wahid Hasyim, 2024)
The sale of vape products has become a rapidly growing industry, with increasing demand from a diverse range of consumers. To keep up with these developments, the existence of an efficient and easily accessible sales information system is crucial for vape store owners. This study aims to implement and design a mobile-based sales information system for Vapestore using Flutter. The system development method used in this research is the iterative software development method. Flutter was chosen as the development platform due to its ability to create mobile applications with responsive user interfaces and efficient cross-platform deployment. The designed information system will include features such as inventory management, customer management, sales report generation, and online payment integration. By using Flutter, it is expected that this application can be easily accessed through various mobile devices, such as smartphones and tablets, allowing store owners to manage their sales efficiently wherever and whenever needed. Additionally, with the online payment integration feature, customers will also experience a more convenient and faster shopping process. This research is expected to provide a positive contribution to vape store owners in improving their operational efficiency and enhancing the customer shopping experience. Furthermore, the results of this study may serve as a reference for future research in the development of more advanced sales information systems that are tailored to the continuously evolving market needs.